Ethylene augments root hypoxia tolerance via growth cessation and reactive oxygen species amelioration - Liu, Zeguang; Hartman, Sjon; van Veen, Hans; Zhang, Hongtao; Leeggangers, Hendrika A C F; Martopawiro, Shanice; Bosman, Femke; de Deugd, Florian; Su, Peng; Hummel, Maureen; Rankenberg, Tom; Hassall, Kirsty L; et al. (Plant physiology (Bethesda), 2022)
Abstract Flooded plants experience impaired gas diffusion underwater, leading to oxygen deprivation (hypoxia). The volatile plant hormone ethylene is rapidly trapped in submerged plant cells and is instrumental for enhanced hypoxia acclimation. However, the precise mechanisms underpinning ethylene-enhanced hypoxia survival remain unclear. We studied the effect of ethylene pretreatment on hypoxia survival of Arabidopsis (Arabidopsis thaliana) primary root tips. Both hypoxia itself and re-oxygenation following hypoxia are highly damaging to root tip cells, and ethylene pretreatments reduced this damage. Ethylene pretreatment alone altered the abundance of transcripts and proteins involved in hypoxia responses, root growth, translation, and reactive oxygen species (ROS) homeostasis. Through imaging and manipulating ROS abundance in planta, we demonstrated that ethylene limited excessive ROS formation during hypoxia and subsequent re-oxygenation and improved oxidative stress survival in a PHYTOGLOBIN1-dependent manner. In addition, we showed that root growth cessation via ethylene and auxin occurred rapidly and that this quiescence behavior contributed to enhanced hypoxia tolerance. Collectively, our results show that the early flooding signal ethylene modulates a variety of processes that all contribute to hypoxia survival. The early flooding signal ethylene contributes to forthcoming hypoxia stress by modulating a plethora of processes including reactive oxygen species amelioration and growth cessation.